Experimental and Bibliometric Analysis of Truncated Cone Fouling Suppression Device for Vortex-Induced Vibration Control in Marine Structures - Noor Idora Mohd Sukarnoor; Wan Mohd Norsani Wan Nik; Ahmad Hussain; Lee Kee Quen; Nur Najahatul Huda Saris; Suriani Mat Jusoh; Fakhratul Ridwan Zulkifli (ASEAN Journal for Science and Engineering in Materials, 2026)
Vortex-induced vibration (VIV) poses a critical threat to the integrity and fatigue life of marine and offshore structures. This study evaluates the effectiveness of a truncated cone fouling suppression device in reducing VIV of a low-mass ratio circular cylinder. Experiments were performed in a circulating water flume at Reynolds numbers ranging from 8,000 to 45,000, using various surface coverage ratios. The vibration amplitude and frequency responses were analyzed to determine suppression performance. Results showed that the device reduced oscillation amplitude by up to 68% within the lock-in region, with optimal suppression observed at 25-50% coverage. This indicates that partial surface modification enhances flow–structure interaction and weakens wake coherence. Furthermore, a bibliometric analysis was integrated to identify research trends and gaps in passive vibration control. The present approach provides both scientific and practical insights for developing low-drag, efficient, and sustainable VIV mitigation strategies in marine engineering.